Cardiorespiratory resuscitation - Salsamendi, María Julia (Cirugía del Uruguay, 1974)
Cardiorespiratory restoration in patients with serious thoraxical injury is based on two groups of measures. The first (to re-establish cardiorespiratory equilibrium) : oro or naso-tracheal intubation, tracheo-bronchial aspiration, !.P.P. breathing, drainage of pneumothorax and evacuation of pleural hemorrhage. In the management of cardiocirculatory recuperation mention is made of pericardiocentesis ( in cardiac obstruction) reposition of volemia and treatment for shock. The practice of surgery is considered appropriate under these circumstances, but only ü it constitutes a step further in obtaining reaction. As a secondary measure (to maintain the cardiocirculatory and respiratory balance obtained) an approach can be made by artificial !.P.P. and surgical treatment of costal flail segment. The first is advisable when employed in treatment of a serious hypoxemia or respiratory difficulty due to lung injury. This is not the case when it is applied as the only means for the stabilization of a parietal flail segment. Three cases are presented and discussed, each having been treat in a different manner. To summarize, good results are obtained by osteo-synthesis with steel thread plus traction; and for parietal stabilization a center medular wiring is considered the most effective treatment in cases of thoraxic injury.